Achieving Financial Goals Through Better Savings Literacy for the Kota Daro II Village Community in Rantau Panjang District, Ogan Ilir Regency, South Sumatera - Yuliani Yuliani; Isnurhadi Isnurhadi; Taufik Taufik; Maulana Maulana (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Financial Services Authority (OJK) faces serious issues when it comes to financial literacy due to the low level of community ability to manage personal finances and MSME business owners. The financial situation of the residents of Kota Daro II Village, Rantau Panjang District, Ogan Ilir Regency, who depend on a variety of businesses for their daily needs and long-term planning. The idea of financial planning includes saving as a crucial component. The goal of this service is to provide education in the form of counseling on understanding the concept of saving, understanding factors that make it difficult to save consistently, appropriate saving techniques, and saving in a variety of investment vehicles in addition to banking. The target audience in this community service activity is 33 people both as households and also MSME actors. The activity model is education in the form of counseling with face-to-face implementation methods in Kota Daro II Village. The event took place on Monday, October 22, 2022, from 9:00 AM to 12:00 PM. Based on the evaluation of community service activities, the results of the activities demonstrate an improvement in understanding for 100% of the activity participants. The ability of the participants to respond to oral questions at the end of the activity demonstrates their level of understanding